Salivary leptin as a potential early diagnostic tumor marker in suspected oral cancer patients - Amir Sabri, Nur Armidha Nadihah; Mustafa, Basma Ezzat; Mokhtar@Makhtar, Khairani Idah; Mohd Ibrahim, Mohamad Shafiq; Subramaniam, Pram Kumar; Abdul Rasheed, Shamim Rahman (Ektodermal Displazi Grubu, 2024)
Leptin a 16-kDa peptide hormone plays an important regulatory role in basal metabolism and food intake. It is considered as a linkage between metabolism and the immune system. It plays a key role in different types of cancer due to its angiogenic, mitogenic, pro-inflammatory, and antiapoptotic properties. The fact that leptin is associated with tumors and is produced and secreted by salivary glands prompted us to investigate the role of salivary leptin in the human salivary gland and evaluate salivary leptin hormone in suspected oral cancer patients and investigate the possible diagnostic relevance of salivary leptin hormone as a potential tumor marker. 36 individuals were included in this study, 20 controls and 16 suspected oral cancer patients. The salivary samples were obtained from both groups using a standardized method and the leptin levels were measured in the salivary samples by using Human LEP (Leptin) ELISA kit. Data analysis was performed using the Mann-Whitney U test for Social Sciences (SPSS version 24). The median leptin level for healthy control is 21.60 (20.26,24.08) pg/ml while it is 32.03 (27.38, 35.09) pg/ml for suspected oral cancer patients. A statistically significant difference in leptin levels is shown in suspected oral cancer patients compared to control. Therefore, this study suggests a promising diagnostic role of leptin hormone as a tumor marker in suspected oral cancer patients.